Controlling the release of indomethacin from glass solutions layered with a rate controlling membrane using fluid-bed processing. Part 1: Surface and cross-sectional chemical analysis - Dereymaker, Aswin; Scurr, David J.; Steer, Elisabeth D.; Roberts, Clive J.; Van den Mooter, Guy (American Chemical Society, 2017)
Fluid bed coating has been shown to be a suitable manufacturing technique to formulate poorly soluble drugs in glass solutions. Layering inert carriers with a drug–polymer mixture enables these beads to be immediately filled into capsules, thus avoiding additional, potentially destabilizing, downstream processing. In this study, fluid bed coating is proposed for the production of controlled release dosage forms of glass solutions by applying a second, rate controlling membrane on top of the glass solution. Adding a second coating layer adds to the physical and chemical complexity of the drug delivery system, so a thorough understanding of the physical structure and phase behavior of the different coating layers is needed. This study aimed to investigate the surface and cross-sectional characteristics (employing scanning electron microscopy (SEM) and time of flight secondary ion mass spectrometry (ToF-SIMS)) of an indomethacin–polyvinylpyrrolidone (PVP) glass solution, top-coated with a release rate controlling membrane consisting of either ethyl cellulose or Eudragit RL. The implications of the addition of a pore former (PVP) and the coating medium (ethanol or water) were also considered. In addition, polymer miscibility and the phase analysis of the underlying glass solution were investigated. Significant differences in surface and cross-sectional topography of the different rate controlling membranes or the way they are applied (solution vs dispersion) were observed. These observations can be linked to the polymer miscibility differences. The presence of PVP was observed in all rate controlling membranes, even if it is not part of the coating solution. This could be attributed to residual powder presence in the coating chamber. The distribution of PVP among the sample surfaces depends on the concentration and the rate controlling polymer used. Differences can again be linked to polymer miscibility. Finally, it was shown that the underlying glass solution layer remains amorphous after coating of the rate controlling membrane, whether formed from an ethanol solution or an aqueous dispersion.